School-Based Prevention in Very Remote Settings: A Feasibility Trial of Methods and Measures for the Evaluation of a Social Emotional Learning Program for Indigenous Students in Remote Northern Australia - Robinson, Gary William; Lee, Eunro; Silburn, Sven Robert; Nagel, Patricia; Leckning, Bernard; Midford, Richard (Frontiers in Public Health, 2020)
Purpose: Skills for Life (SFL) is a social-emotional curriculum for Indigenous middle school students that was co-developed with educators and community members in a remote community of northern Australia. This preliminary study aimed to test the feasibility of processes and methods of data-gathering, the reliability of youth self-report measures, and to identify the direction of effects for an evaluation of a longer-term pilot of the curriculum. Design/Methodology/Approach: Indigenous Students in years 7–9 of a remote school participated in SFL over 2 years. The Strengths and Difficulties Questionnaire (SDQ), Kessler 6 (K6), and a purpose-designed Connected Self Scale (CSS) were administered to 63 students pre- and post-program. Findings: Only the K6, Prosocial behavior (SDQ), and two CSS subscales showed sufficient internal consistency for analysis. Change was positive but non-significant for SDQ and CSS. There was evidence of a dosage effect: students receiving the intervention over 2 years showed greater reduction in psychological distress than other students. There was no evidence of iatrogenic effects. Conclusions: The feasibility pilot is a critically important phase in the development of evaluation design and cjhoice of evaluation measures for challenging remote settings. This study found that evaluation of SFL with culturally and linguistically distinct Indigenous middle school students using self-report measures is feasible. However, the SDQ may not be suitable for this project. High levels of psychological distress suggest the need to investigate sources of life stress and potential supports for adolescent resilience in this context. This preliminary pilot aimed to trial methods and measures for evaluation of a social-emotional curriculum developed specifically for remote Australian Indigenous students who are at risk of poor psychosocial outcomes. No studies have examined the appropriateness of standardized self-report measures for evaluation of SEL with this student population in remote school settings.